Extraction Fuel During Hydro-distillation Modifies Eucalyptus Essential Oil Yield, Phytochemical Quality, and Capital Cost - Sharma, Arun Dev; Kaur, Inderjeet (Current Indian Science, 2023)
Introduction Plant-based essential oils are usually extracted using the hydro-distillation process. During this process type of fuel is a major factor that regulates yield, aromatic quality, and capital cost. AIM: This study aimed to examine the distillation of eucalyptus essential oil using Fire word (FW), Liquefied Petroleum Gas (LPG), and Electric Filament (EF) derived energy as fuels. Eucalyptus fresh leaves were used to extract the essential oil. Methods Several parameters were examined, including the yield of oil, total phenolic content and total antioxidant activity, and total capital cost of each procedure. The results revealed that EF-based hydro-distillation reduced the cost of essential oil production many times compared to FW and LPG-based fuels. Results Using EF, essential oil quality also increased considerably in terms of total phenolic content (1.49 mg GAE/ml) and total antioxidant activity (4.2 mg AE/ml). GC-FID analysis discovered the occurrence of 1,8 cineole as a major component in eucalyptus essential oil. Conclusion To conclude, EF-based fuel offers significant advantages over traditionally used fuels to hydro-distill eucalyptus essential oil in cosmetic and pharma-based industries.
Keywords: Eucalyptus